'Coop' edges Honeyfield for JC award (Raton Range Raton, New Mexico, 1989)
Newspaper article on Eric Honeyfield and Michael Cooper who were both nominated for 1989 Outstanding Young New Mexican award.
Master list item #: 6
File location is in the Raton file Cabinet
Keywords: Honeyfield, Eric; New Mexico Jaycees; UNM; NBA; NCAA; Childrens Hospital; Biography; Local History; Jaycee; Awards; City Manager; Nominations; Basketball; Fund raising; Raton, New Mexico; Las Cruces, New Mexico; Los Angeles, California; Corrales, New Mexico; Santa Fe, New Mexico; Albuquerque, New Mexico